2005
DOI: 10.1111/j.1365-2664.2005.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of soil macrofauna across a Scottish land‐use intensification gradient: influences of habitat quality, heterogeneity and area

Abstract: Summary1. Land-use intensification strongly influences biodiversity by altering habitat heterogeneity, the distribution of habitat types and their extent. This study explores these effects within mixed semi-natural/agricultural mosaic habitats in Scotland, examining the effect of land-use intensification on the soil macrofauna at point (m 2 ), landscape (km 2 ) and regional (> 1 km 2 ) scales. 2. The soil macrofauna in six 1-km 2 sampling areas (land-use units; LUU) were sampled using a combined hand-sorting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 22 publications
5
36
0
1
Order By: Relevance
“…The diversity, abundance, biomass and density of soil fauna has been used as indicator of natural or anthropogenic impacts on terrestrial ecosystems because they are strictly correlated with physical, chemical, and microbiological soil attributes (Decaëns et al, 2004;Eggleton et al, 2005). This is a quite simple, easy, and economical procedure employed for assessment of the taxonomic diversity at order, class or key species level.…”
Section: Faunal Indicatorsmentioning
confidence: 99%
“…The diversity, abundance, biomass and density of soil fauna has been used as indicator of natural or anthropogenic impacts on terrestrial ecosystems because they are strictly correlated with physical, chemical, and microbiological soil attributes (Decaëns et al, 2004;Eggleton et al, 2005). This is a quite simple, easy, and economical procedure employed for assessment of the taxonomic diversity at order, class or key species level.…”
Section: Faunal Indicatorsmentioning
confidence: 99%
“…Comparatively little is known, however, about the impact of landscape-scale habitat heterogeneity on species, such as soil invertebrates, that operate at Wne spatial scales (e.g. centimetres-metres) and are of restricted mobility (Chust et al 2003;Dauber et al 2005;Eggleton et al 2005;Joschko et al 2006).…”
mentioning
confidence: 99%
“…Anthropogenic forest fragmentation (Didham et al 1998a;Davies et al 2000;Andresen 2003), conversion to silviculture or agriculture (Eggleton et al 2002;Dunn 2004) and land-use intensiWcation (Lawton et al 1998;Benton et al 2003;Jones et al 2003;Eggleton et al 2005) alter the size and heterogeneity of habitats. These anthropogenic drivers can create landscapes that are a mosaic of habitats; these, in turn, can inXuence species diversity depending on how each species perceives this environmental heterogeneity (Tews et al 2004).…”
mentioning
confidence: 99%
“…Such intensification results in the removal of structural elements of the matrix, for example the removal of paddock trees (Maron, 2005), as well as resulting in direct mortality for species susceptible to chemical inputs. The impacts of such loss and alteration of matrix habitat are evident at both the paddock and the landscape scale (Eggleton et al, 2005;Tscharntke et al, 2005). Simulation studies have demonstrated that matrix quality can affect the ability of species to traverse the landscape by influencing the effectiveness of stepping stones and corridors (Baum et al, 2004), and paddock trees in particular have been shown to provide nesting and feeding habitat (Law et al, 2000;Lumsden et al, 2002;Manning et al, 2004;Lumsden and Bennett, 2005) and act as stepping stones between native vegetation remnants (Fischer and Lindenmayer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Largescale shifts to intensive land uses in regions long used for traditional, more extensive agriculture have been implicated in such declines, particularly in Europe (Fuller et al, 1995;Chamberlain et al, 2000;Newton, 2004;Eggleton et al, 2005). The everincreasing pressure for greater production efficiency in farming systems is continuing to drive the trend toward more intensive agricultural practices (Mansergh et al).…”
Section: Introductionmentioning
confidence: 99%